Management of overactive bladder review: the role of percutaneous tibial nerve stimulation (Medical Journal of Indonesia, 2016)
Overactive bladder (OAB) is a common condition that is experienced by around 455 million people (11% of the world population) and associated with significant impact in patients' quality of life. The first line treatments of OAB are conservative treatment and anti-muscarinic medication. For the refractory OAB patients, the treatment options available are surgical therapy, electrical stimulation, and botulinum toxin injection. Among them, percutaneous tibial nerve stimulation (PTNS) is a minimally invasive option that aims to stimulate sacral nerve plexus, a group of nerve that is responsible for regulation of bladder function. After its approval by food and drug administration (FDA) in 2007, PTNS revealed considerable promise in OAB management. In this review, several non-comparative and comparative studies comparing PTNS with sham procedure, anti-muscarinic therapy, and multimodal therapy combining PTNS and anti-muscarinic had supportive data to this consideration.